O programa judicial de acompanhamento do desmatamento na Amazônia e os limites da efetividade das decisões dos tribunais superiores - Erthal, Alessandra Antunes (My University, 2026)
This dissertation examines the crisis of effectiveness of Brazilian environmental jurisdiction in light of the socio-environmental complexity of the Amazon, focusing on the period from 2019 onward, marked by the intensification of deforestation and significant institutional changes in federal environmental policy. It is based on the hypothesis that the traditional jurisdictional model, structured under a rationalist and abstract paradigm, proves insufficient to address structural environmental conflicts, often operating as a normative promise detached from territorial reality. The research adopts a qualitative approach, combining bibliographic analysis with the examination of decisions issued by the higher courts concerning Environmental Law and the Amazon, seeking to identify patterns of decisional abstraction and the limits of the prevailing procedural rationality. The conception of the judicial decision as a punctual and self-sufficient act is problematized, advocating for a form of jurisdiction more sensitive to the factual, institutional, and territorial contingencies that characterize contemporary environmental conflicts. As an extension of this analysis, the Judicial Program for Monitoring Deforestation in the Amazon (PROJADA), established by the National Council of Justice, is examined as a mechanism aimed at monitoring and ensuring the implementation of environmental judicial decisions, assessing its potential and limitations as an institutional response to the crisis of effectiveness of environmental jurisdiction. It is concluded that overcoming ineffectiveness requires the incorporation of a procedural rationality committed to reality, strengthening structural mechanisms for monitoring, enforcement, and oversight of judicial decisions. [resumo fornecido pelo autor]
Esta dissertação examina a crise de efetividade da jurisdição ambiental brasileira diante da complexidade socioambiental amazônica, com recorte temporal a partir de 2019, período marcado pelo agravamento do desmatamento e por transformações institucionais relevantes na política ambiental federal. Parte-se da hipótese de que o modelo jurisdicional tradicional, estruturado sob um paradigma racionalista e abstrato, revela-se insuficiente para enfrentar conflitos ambientais de natureza estrutural, operando frequentemente como promessa normativa dissociada da realidade territorial. A pesquisa adota abordagem qualitativa, com análise bibliográfica e exame de julgados dos tribunais superiores relacionados ao Direito Ambiental e à Amazônia, buscando identificar padrões de abstração decisória e limites da racionalidade processual vigente. Problematiza-se a concepção da sentença como ato pontual e autossuficiente, defendendo-se a necessidade de uma atuação jurisdicional mais sensível às contingências fáticas, institucionais e territoriais que caracterizam os conflitos ambientais contemporâneos. Como desdobramento da análise, examina-se o Programa Judicial de Acompanhamento do Desmatamento na Amazônia (PROJADA), instituído pelo Conselho Nacional de Justiça, enquanto mecanismo voltado ao monitoramento e à concretização das decisões judiciais ambientais, avaliando suas potencialidades e limites como resposta institucional à crise de efetividade da jurisdição ambiental. Conclui-se que a superação da inefetividade exige a incorporação de uma racionalidade processual comprometida com a realidade, com fortalecimento de instrumentos estruturais de acompanhamento, execução e controle das decisões judiciais. [resumo fornecido pelo autor]
Keywords: Direito ambiental - Amazônia; Processo estrutural; Princípio da efetividade; Proteção ambiental - Amazônia - Aspectos jurídicos; Desmatamento - Amazônia - Aspectos jurídicos; Environmental law - Amazônia (Brazil); Structural process; Principle of effectiveness; Environmental protection - Amazônia (Brazil) - Legal aspects; Clearcutting - Amazônia (Brazil) - Legal aspects